Raw starch-digesting amylase from saccharomycopsis fibuligera 2074 isolated from bubod starter - Fronteras, Jennifer Pena; Bullo, Lani Lee R. (2017)
Eight microbial isolates from bubod starter purchased from the Philippine National Collection of Microorganisms displayed amylolytic activity on raw sago starch indicating that they are possible sources of raw starch-digesting amylases (RSDA). Saccharomycopsis fibuligera 2074 showed the highest activity followed by Saccharomycopsis bubodii 2066 as determined through Dinitrosalicylic Acid Method. For Saccharomycopsis fibuligera 2074, maximum amylase production was obtained from 36-hour culture using 1% raw sago starch as carbon source under static incubation. The enzyme was purified via two-step purification protocol involving ammonium sulfate precipitation and diethylaminoethyl cellulose chromatography to give a specific activity of 180.49 U/mg and 2.57 purification fold. Further characterization of the enzyme showed that the amylase activity was optimum at pH 6 and temperature of 40°C. Although the enzyme was inhibited by Cu2+, Zn2+, and Al3+, it was activated by Ca2+, Fe3+, Ba2+, phenylmethylsulfonyl fluoride and ethylenediaminetetraacetic acid. On the other hand, iodoacetic acid, K+, Cd2+, and Mg2+, showed no significant effect on the amylase activity. Saccharomycopsis fibuligera 2074 showed to be a promising source of RSDA to allow the direct and less costly conversion of raw sago starch to glucose.